2016
DOI: 10.1039/c6cc01621a
|View full text |Cite
|
Sign up to set email alerts
|

Iron–naphthalenedicarboxylic acid gels and their high efficiency in removing arsenic(v)

Abstract: Metal-organic gels (MOGs) of three-dimensional (3D) networks comprising nanosheets of ∼30 nm thickness and square-micrometer in size were easily produced via coordination interactions of iron (Fe(3+)) and 1,4-naphthalenedicarboxylic acid (NDC). Such MOGs exhibit ultrahigh removal of arsenic(v) in water, with the adsorption capacity of 144 mg g(-1), dramatically superior to those of the recently reported Fe-based inorganic and organic adsorbents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 34 publications
6
24
0
Order By: Relevance
“…The limit of detection (LOD), defined as ac hange of 10 %i ne mission intensity, [23] was calculated to be 3.50 mmol L À1 .T he sensing of Cu 2 + ions by other PL nanomaterials, such as Cd ots, has also been reported. [24] Although the LOD achieved by the fullerenols in the current study is not the lowest among the reported results, [25] the LOD value is considered sufficient to detect the overbalance of Cu 2 + ions in environmental science, and even in food chemistry when considering the high biocompatibility of fullerenols. More importantly,t hesem olecules could be used as multifunctional materials in biology and life sciences as fullerenols show important bioactivities, such as radical scavenging, andc an generate reactive oxygen speciesu nder photoirradiation.…”
Section: Spectroscopic Propertiesmentioning
confidence: 60%
See 1 more Smart Citation
“…The limit of detection (LOD), defined as ac hange of 10 %i ne mission intensity, [23] was calculated to be 3.50 mmol L À1 .T he sensing of Cu 2 + ions by other PL nanomaterials, such as Cd ots, has also been reported. [24] Although the LOD achieved by the fullerenols in the current study is not the lowest among the reported results, [25] the LOD value is considered sufficient to detect the overbalance of Cu 2 + ions in environmental science, and even in food chemistry when considering the high biocompatibility of fullerenols. More importantly,t hesem olecules could be used as multifunctional materials in biology and life sciences as fullerenols show important bioactivities, such as radical scavenging, andc an generate reactive oxygen speciesu nder photoirradiation.…”
Section: Spectroscopic Propertiesmentioning
confidence: 60%
“…These conclusions gain support from previous reports. [24][25][26] The association constant (K)o ft he complexes can be obtained from the Benesie-Hildebrand Equation (1)…”
Section: Spectroscopic Propertiesmentioning
confidence: 99%
“…Ferrous magnetic nanoparticles (MNPs) are outstanding adsorbents for iAs removal because of the strong and irreversible interaction between iAs and iron oxide1314. Superparamagnetic Fe 3 O 4 , Fe 3 O 4 -graphene composites, hematite-coated Fe 3 O 4 , and polystyrene-supported nano-Fe 3 O 4 have been exploited to remove iAs from water samples15161718.…”
mentioning
confidence: 99%
“…Such novel functionalized MOGs with self‐healing property and good conductivity are potentially used in the field of energy storage . Xerogels or aerogels, for example, prepared from MOGs, with porous structures and iron component are a class of good adsorbents for As(V) removal, which have been proved previously . Polycyclic aromatic hydrocarbons are common gelators, however, they are vital environmental pollutants.…”
Section: Introductionmentioning
confidence: 93%
“…Supramolecular self‐assembly has been proved to be a promising strategy for preparing functional materials . Metal‐organic gels (MOGs) can be prepared through self‐assembly of ligands with metal ions or metal clusters, which have attracted significant interest due to their potential applications in diverse areas such as catalysis, energy storage, template synthesis, and environmental technology . The porous structures and the introduced metal ions or metal clusters are the mayor factors which endow MOGs applications in these fields .…”
Section: Introductionmentioning
confidence: 99%